Use of colorimetry in a new LAMP test for the visual detection of Chlamydia abortus in domestic ruminants - Aragón-Lopez , Carlos-Eduardo; Luna-Nevárez, Pablo; Palomarez-Reséndiz, Erika-Gabriela; Rojas-Arzaluz, Mario; Sánchez-Castro, Miguel-Ángel; Leyva-Corona, José-Clemente; Morales-Pablos, Marcela-Ivone (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Chlamydia abortus is the etiological agent of ovine enzootic abortion (OEA), a worldwide disease that significantly impacts to cattle, sheep, and goat production. This bacterium causes abortions during the last third of gestation and its zoonotic. The lack of prior symptoms before an abortive event complicates the clinical diagnosis of OEA and its differentiation from other infections, highlighting the need for an effective diagnostic tool. Some conventional diagnostic methods could be accurate, but in some cases require expensive equipment and highly trained personnel, limiting their field application. Under this context, the loop-mediated isothermal amplification (LAMP) emerges as an accessible and efficient alternative, capable of operating at a constant temperature and simplifying the interpretation of results visually through colorimetry. Objective: To validate a new LAMP assay using colorimetry for the visual detection of Chlamydia abortus in domestic ruminants. Method: Fifty-six DNA samples collected from ruminants with abortion history were used as biologic control of reference. LAMP specific primers were designed for the TARP gene of C. abortus. A colorimetric assay was validated for the LAMP test of C. abortus (crLAMP-Chla). The concordance (K), sensibility (Se) and specificity (Sp) parameters of crLAMP-Chla were calculated considering real time PCR as reference. Results: The crLAMP-Chla detected the pathogen from 15 minutes at 65 °C, even at low DNA concentrations. The K, Se and Sp values were 1, 100% and 100% (P=0.05) respectively. Conclusion: This methodology represents a significant advancement for the control of C. abortus in ruminants, providing an accessible and efficient diagnostic tool to improve public and animal health.